Effect of four training systems on the temporal dynamics of downy mildew in two grapevine cultivars in southern Brazil - de Bem B.P.* (2016)
© 2016, Sociedade Brasileira de Fitopatologia.The aim of this study was to evaluate the temporal dynamics of downy mildew epidemics under four training systems: vertical shoot positioning (VSP), Geneva Double Curtain (GDC), Simple Curtain (SC) and Tendone in two cultivars (‘Cabernet Sauvignon’ and ‘Merlot’). Experiments were conducted at commercial vineyards in southern Brazil, during the 2012–2013 and 2013–2014 growing seasons. Downy mildew incidence and severity were quantified on a weekly basis from the first symptoms appearance until harvest. Training systems and cultivars were compared based on the following variables of downy mildew progress curves: a) beginning of symptoms appearance (BSA); b) maximum disease incidence and severity (Imax, Smax); c) time to reach maximum disease incidence/severity (TRMDI and TRMDS); and d) area under incidence and severity disease progress curve (AUIDPC and AUSDPC). The training systems significantly affected AUSDPC and Smax. AUSDPC was lowest in the VSP system in all cultivars and growing seasons. In addition, ‘Merlot’ showed significantly lower AUIDPC and AUSDPC than ‘Cabernet Sauvignon’ in both growing seasons. The Tendone and GDC systems showed significantly higher AUSDPC in all cultivars and growing seasons. Our results suggested that the use of the VSP system contributes to reduce downy mildew severity on ‘Merlot’ and ‘Cabernet Sauvignon’ in southern Brazil.